Religious Diversity and Early Modern English Texts : Catholic, Judaic, Feminist, and Secular Dimensions - Marotti, Arthur F., 1940- (Book collections on Project MUSE., 2013)
In this book, the editors present thirteen essays that examine the complex religious culture of early modern England. Emphasizing particularly the marginalized discourses of Catholicism and Judaism in mainstream English Protestant culture, the authors highlight the instability of an official religious order that was troubled not only by religious heterodoxy but also by feminist and secular challenges. North American and Israeli scholars present essays on a wide range of subjects all assumed to be "marginal" but which in a real sense were central to the religious and cultural life of the Protestant English nation. Using critical methods ranging from historical analysis, deconstruction, feminist inquiry, and intertextual interpretation to pedagogical experimentation, contributors offer analyses in five sections: Minority Catholic Culture, Figuring the Jew, Hebraism and the Bible, Women and Religion, and Religion and Secularization. Essays reveal new aspects of familiar texts such as Shakespeare's King Lear and The Merchant of Venice, the psalm translations by Sir Philip Sidney and the Countess of Pembroke, Christopher Marlowe's dramas, George Herbert's poetry, Aemelia Lanyer's Salve Deus Rex Judaeorum, and John Milton's Samson Agonistes. They also call attention to works such as the mid-sixteenth-century play The Historie of Jacob and Esau, William Blundell's Catholic antiquarian writing, the series of paintings portraying the religious institute of Mary Ward, and funeral sermons for religiously active women. -- Publisher website.